Does stress increase risk of breast cancer? A 15‐year prospective study. Issue 8 (4th May 2018) - Butow, Phyllis; Price, Melanie; Coll, Joseph; Tucker, Katherine; Meiser, Bettina; Milne, Roger; Wilson, Judith; Heiniger, Louise; Baylock, Brandi; Bullen, Tracey; Weideman, Prue; Phillips, Kelly‐Anne; et al.
Abstract: Objective: The possible impact of stress on cancer incidence remains controversial. We prospectively evaluated associations between life event stressors, social support, personality characteristics (optimism, anger control, antiemotionality), and risk of developing primary breast cancer (BCa), in women at increased familial risk of BCa. Methods: A prospective cohort, repeated measures design was used. Recruitment was through the Kathleen Cuningham Foundation Consortium for Research into Familial Breast Cancer, which collects genetic, epidemiological, and clinical data from Australasian families with multiple BCa cases. Acute and chronic stressors for the prior 3 years and psychosocial, clinical, and epidemiological variables were measured at cohort entry and at 3‐yearly intervals. Cox proportional hazard regression analysis controlling for BCa risk factors and familial clustering was undertaken. The primary outcome was histopathologically confirmed BCa (invasive or ductal carcinoma in situ, including occult cases diagnosed during risk‐reducing mastectomy). Results: Of 3595 consecutive women invited to participate, 3054 (85.0%) consented. Of these, 2739 (89.7%) from 990 families (range 1‐16 per family) completed at least 1 assessment point. During the study, 103 women were diagnosed with BCa. No stressor or psychosocial variable or interaction between them was significantly associated with BCa in unadjusted or adjusted models (total acute stressors HR = 1.03 [0.99‐1.08], P  = .19; total chronic stressors HR = 1.0 [0.90‐1.11], P  = .98). Conclusions: This study did not demonstrate an association between acute and chronic stressors, social support, optimism, antiemotionality or anger control, and BCa risk. Women should focus on proven methods of BCa risk reduction.